Determination and Removal of Toxic Anions from Guyana’s Aquatic Environment: Green and Sustainable Management - Brij Bhushan Tewari (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 2, 2023)
The COVID-19 pandemic has negatively affected lives in the world. Currently the world is in need for green, sustainable form of living and practices in order to balance this crisis. The COVID-19 pandemic has affected many political, economic, social and environmental challenges. Standard analytical procedures that are based on colorimetric facilitated the determination of PO43- and NO3- in the ground and surface waters from the three (3) counties of Guyana. Phosphates and nitrates beyond their permissible levels in natural waters can pose significant threats to the aquatic environment, its inhabitants, and the health of humans and terrestrial animals. This study aims to investigate the use of metal (nickel, cadmium, cobalt) ferrocyanides (octahedral complexes that facilitate adsorption of anions primarily on its two divalent transitional metals) as adsorbents to facilitate the removal of the aforementioned anions. The outcomes showed that nickel ferrocyanide is the most effective adsorbent for treating ground and surface waters that contain high levels of PO43-, while it was also the most effective adsorbent for treating surface waters that contained NO3-. Fixed volumes of water samples were treated with 50 mg, 100 mg, and 150 mg of the adsorbent. The computations of the correlation coefficients showed that there were both positive and negative correlations in some of the cases, which meant that raising the dosage of the adsorbent increased and decreased adsorption, respectively. Adsorption investigations were facilitated by the use of Langmuir plots and adsorption isotherms, although in some cases, the generic look of these isotherms was not noticed. Possible explanations for this occurrence are discussed in greater depth in the paper. The use of cobalt ferrocyanide to treat groundwater and remove PO43- is not advised based on observations highlighted in the report, and the use of cadmium ferrocyanide to facilitate the removal of NO3- is not advised either due to the potential formation of Co3(PO4)2 and Cd(NO3)2, respectively, which negatively impacted the results. Technologies like those studied in this research project should be explored and studied more in-depth (particularly with regards to the stability of the adsorbents) with regards to the treating of ground and surface water supplies, to facilitate the removal of PO43- and NO3-, since the results observed, though on a small scale, can be seen to move us closer towards a green and sustainable environment, inclusive of safeguarding the health of the Worlds’ people and expanding the scope of cost-effective and simple methods that aid in the removal of anions from natural waters. Green chemistry creates technologies that prevent further damage to environment and human health, while sustainable chemistry is referrers to the production of chemicals that reduce the use of hazardous substances.